EFEKETIFITAS MONITORING DAN EVALUASI PEMBELAJARAN DARING DENGAN MENGGUNAKAN LMS QUIPPER SCHOOL DI SMAN 1 PANJI SITUBONDO: SMAN 1 PANJI SITUBONDO - ONI PAMBAGYO TRIANTORO (Mitra Pendidikan, 2021)
Monitoring and evaluation is a process of monitoring and assessing the progress and success of an educational activity, especially in improving the performance of teachers who can support a good learning process. The purpose of this study was to determine the effectiveness of monitoring and evaluation of teacher performance and online learning using the Quipper School Learning Management System (LMS) at SMAN 1 Panji Situbondo, and to find out what obstacles were encountered in implementing online learning at SMAN 1 Panji Situbondo. . The approach used in this research is to use a quantitative and qualitative descriptive approach. Subjects in this study were subject teachers. The data collection technique is using the results of statistical analysis using the Quipper School application, interviews, observations and documentation. This type of research is Classroom Action Research (CAR). CAR is an observation of learning activities in the form of an action, which is deliberately raised and occurs in a class together. Wina Sanjaya (2011) defines CAR as a process of studying learning problems in the classroom through self-reflection in an effort to solve these problems by carrying out various planned actions in real situations and analyzing any effects of the treatment. Suharsimi Arikunto (2007) explains that in collaborative research, the party who takes the action is the class teacher itself, while the researcher is the researcher who observes the ongoing process of action. The classroom action research model used in this study refers to the Kemmis & McTaggrat Model which consists of four components, namely planning, acting, observing and reflecting. The results of this study indicate that the process of implementing the monitoring and evaluation of teacher performance runs effectively and efficiently using Quipper School's LMS and various implementation techniques and compares the results, evaluates learning programs, to find out how far online learning has gone well and optimally, and reduce the impact of losses from its implementation and improve teacher performance. Constraints faced during the implementation process A small number of teachers, especially those approaching retirement, have difficulty using the QS LMS, and there are a number of students who have difficulty accessing online learning because they do not have quotas and poor internet signals.